Mentoring in teacher education: An experience that makes a difference for college of education student teachers - Mercy Ifunanya Ani; Ifeoma Roseline Iketaku; Peter Chika Uzosike (Northern Negros State College of Science and Technology (NONESCOST), 2021)
This study sought the perception of College of Education students on the importance of mentoring, in the teacher education program at Enugu State College of Education Technical. The study also examines the roles that mentors and mentees play in a mentoring relationship and how they interconnect. The study was a descriptive study guided by two research questions and one hypothesis. The population comprised 153 Postgraduate diploma in education students in the College during the 2017/2018 academic year participated in the study. The instrument for data collection was a designed researchers' structured questionnaire in three parts - A, B, and C. part A contained information on respondents' bio-data; part B elicited information on the roles played by mentors who have experienced trained teachers as mentors to the mentees while part C sought information on the strategies used in mentoring the college students. Data were analyzed using frequency counts, percentages, mean, and Pearson Product Moment Correlation statistics. Based on the findings, some recommendations were made.